Investigating a Professional Development School Model of Teacher Education in Canada - Buzza, Dawn; Kotsopoulos, Donna; Mueller, Julie; Johnston, Megan (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
We examined the effectiveness of a professional development school model of teacher education in Canada. Teacher education candidates responded positively to program features related to sustained participation and collaboration in school communities throughout the year. Their efficacy beliefs about developing professional knowledge were most strongly related to the school component of the program. This highlights the importance of careful selection and preparation of associate teachers where teacher candidates are placed in only one school.